Spectroscopy of Electrified Interfaces with Broadband Sum Frequency Generation: From Electrocatalysis to Protein Foams - Braunschweig, Björn; Mukherjee, Prabuddha; Kutz, Robert; Rumpel, Armin; Engelhardt, Kathrin; Peukert, Wolfgang; Dlott, Dana; Wieckowski, Andrzej (Vibrational Spectroscopy at Electrified Interfaces, 2013)
This chapter focuses on the application of vibrational sum frequency generation (SFG) spectroscopy to study the molecular structure of electrode‐electrolyte and electrified liquid‐gas interfaces. Vibrational SFG is inherently interface specific because a second‐order process such as SFG is not allowed in the bulk of materials with inversion symmetry. The development of direct ethanol fuel cells demands an in‐depth understanding of ethanol's electrooxidation reactions. With recent advances in the practical design of alkaline fuel cells, a thorough understanding of the ethanol electrooxidation mechanism in alkaline media is now more important than ever. The chapter provides novel insights into this mechanism by examining new data on surface‐adsorbed reaction intermediates at fuel cell relevant conditions. Foams are materials of particular importance since they have a broad range of applications such as metal foams for light‐weight structures, polymer foams for thermal insulation, as well as in textured food product
Keywords: Electrooxidation reactions; Ethanol fuel cells; Electrified interfaces; Electrocatalysis; Vibrational sum frequency generation (SFG); Protein foams; Spectroscopy